Corruption Schemes in the Supply of Food to the Army during the First World War: the Example of the Yenisei Province - O. M. Dolidovich (Научный диалог, 2018)
A particular case of machinations with food for the army during the First World War is considered. It is reported that in the autumn of 1916 the authorized representative of the Ministry of Agriculture in Western Siberia, A.A. Mitarevsky, sent his representative Novikov to the north of the Yenisei province to purchase a part of the Turukhansk fish. The agent made a deal with local wholesalers P.A. and F.A. Tonkonogov and G. E. Kucherenko at a cost much higher than the market average. Being large fish producers in the Yenisei Uyezd, the Tonkonogovs and Kucherenko bought all fish from fishermen and sold it to Novikov at the maximum price. The situation provoked outrage among local traders, cooperative organizations and the population. To ensure competitive conditions in the fish market to smaller entrepreneurs, Yenisei Governor Ya. G. Gololobov intervened to supply fish to the townspeople at affordable prices. As a result, the terms of the transaction were canceled. The author concludes that attempts to implement such corruption schemes have caused material damage to the treasury, demonstrated the immoral and criminal behavior of many traders and officials, led to an increase in discontent among the population and a general negative attitude towards institutions of power and business.